Espaços de refúgio em Pirenópolis: uma análise fenomenológica e sensorial do habitar na natureza - Furtado, Maria Cristina de Oliveira (2018)
The present master thesis deals with the spaces of refuge existing in the surroundings of the city of Pirenópolis and what are the material and symbolic elements that bring to these places an atmosphere of cosiness and peace. In big cities, man is increasingly disconnected from nature and therefore some people seek to inhabit less urbanized places. Among the motivations is the feeling of security, decreasing in the city. The nature that inspired danger today is the place of protection of modern life. The theoretical discussion covers several areas of study that are in line with the architectural phenomenology approach. Within this context, the philosopher Gaston Bachelard and architect Christian Norberg-Schulz form the basis of the analysis methodology. A tectonic expression and the sensorial aspects of the complementary spaces or theoretical referentials, being important in the realized analyzes. All of them are in tune with the postmodern paradigms of contemporary dwelling, where the object of study is located. The data gathering was carried out through bibliographical, documentary and field research. The interviews are of the type unstandardized and were made with residents of the spaces of refuge. In the final chapter, the analysis of three houses was first carried out, detailing the information about them. In a second moment, the analysis is based on the outstanding elements of the theoretical reference, where besides the three spatialities highlighted, there are also symbolic and sensorial aspects of other raised domestic refuges. In this way, the research proposed to understand ways of living that are in contact with nature and that establish a deep connection between the inhabitant and the place. It is also observed how the theories related to the phenomenology of the architecture are present in the spaces studied.